Studying the trajectories and mediators of old-age problematic alcohol use and the agency of older persons - Jemberie, Wossenseged Birhane; Padyab, Mojgan; Snellman, Fredrik; Eriksson, Malin (Umeå University, 2023)
The study sought insight into the experiences and perspectives of older persons on ageing, alcohol use, treatment, and recovery from an alcohol problem, as well as their understanding of what healthy ageing entails. The study, hence, focused on the subjective experiences of older persons, for an understanding of the challenges and strengths they face in relation to alcohol use and healthy ageing. The dataset consists of 10 semi-structured interviews.

In the interview with eight men and two women aged between 61 and 73 years, we explored their perspectives and experiences of ageing, alcohol use and problems, treatment and alcohol recovery.

The interviews were conducted online through Zoom. Participants joined online or dialed the Zoom number. Each interview lasted in average 101 minutes (between 74 and 128 minutes). The interviews were audio recorded and transcribed. Interview language was Swedish.

Data analysis was performed on the transcribed text in the original language. The text was 207 A4 pages long, 127663 word count (speakers role). It was saved as PDF/A format with the file name "interaction-between-alcohol-and-ageing-and-personal-agency-of-older-persons.pdf"

**********
The participants were interviewed:

1st: About their experience and perception of ageing. Questions included:
* What does getting older mean for you?
* What does healthy ageing or ageing well mean for you?
* Which factors do you think contribute to healthy ageing?
* What has changed in relation to you getting older (in general, and specifically with regard to your health, social situation etc.)?
* and other questions

2nd. About their alcohol use:
* How old were you when you had your first drink? How did it feel?
* How would you describe your relationship with alcohol? Tell me how it looked like in the past from when you were younger until you decided to seek treatment?
* How would you describe your current relationship with alcohol?
* Has anything changed since you received treatment for alcohol? Describe what you have noticed...
* How do you think alcohol and getting older are related? Has your alcohol use contributed to your ageing in a positive or negative way? Tell me more on...
* When you think about things you want to maintain as you get older, how do you think alcohol has affected them?
* What has changed with regard to your ageing since you have changed your alcohol consumption/received treatment, etc...(depending on the interview response)?

There were several other follow up questions based on the participants answer.

Finally we asked questions on information on age, gender, civil status. Education, main source of income in the past 12 months, household income’s ability to cover living cost, perception of current health, perception of current health compared to others of the same age.

I det här datasetet ingår 10 semistrukturerade intervjuer om samspelet mellen åldrande, hälsa, alkoholvanor och personers aktörskap i detta samspel. För en utförlig beskrivning, besök den engelska versionen av denna katalogpost.

Vänligen besök den engelska webbplatsen för denna katalogpost.
En studie av samspelet mellan åldrande, hälsa, alkoholvanor, och personers aktörsskap i detta samspel
PAU-Old
Keywords: Aged; Äldre; AGEING; ÅLDRANDE; Middle Aged; Medelålders personer; Alcohol-Related Disorders; Alkoholmissbruk; ADDICTION; MISSBRUK; INTERVIEWS (DATA COLLECTION); INTERVJU (DATAINSAMLING); Healthy Aging; Hälsosamt åldrande; SUBSTANCE USE; SUBSTANSANVÄNDNING; ALCOHOL USE; ALKOHOLANVÄNDNING; Medication and treatment; Medicinering och behandlingar; General health and well-being; Allmän hälsa och välbefinnande; Elderly; Äldre; Drug Abuse and Addiction; Beroendelära och missbruk; Gerontology, specialising in Medical and Health Sciences; Gerontologi, medicinsk/hälsovetenskaplig inriktning; Social Work; Socialt arbete; Drug abuse, alcohol and smoking; Drogmissbruk, alkohol och rökning